Implementation of Finite State Automata in Graphic Design Class Process Online - Hakim, Valianda; Gata, Windu; Rahayu, Sri; Setiawan, Hendra; Novitasari, Hafifah Bella (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2022)
The development of technology is growing rapidly, the number of increasingly sophisticated inventions can also help humans in carrying out their activities, one of which is online classes, especially graphic design from various official organizers such as from coursera, udemy, and other organizers. Online graphic design classes are currently in great demand by the general public, especially at the school level, some have to pay a certain nominal, there are also free ones to access the class, besides that the classes offered are starting to vary, ranging from the beginner level to the advanced level also with certain software such as Adobe Photoshop, Figma, and other design applications and also with different systems, online or offline, graphic design is much needed, especially in the world of work such as printing, advertising and other fields. In this study, it was designed by using the FSA (Finite State Automata) method with the TYPE of NFA (Non-deterministic Finite Automata) to help students in the process of online graphic design classes starting from registration on the website to getting a class certificate so that students do not feel confused about what to do after registering, and is expected to make students understand in the process of online graphic design classes, The results of using FSA with nfa type can help students to better understand the flow of the registration process for online graphic design classes, with the creation of an FSA with this type of NFA is also expected to help students in registering online to get a certificate because they have attended an online graphic design class. Keywords : desain grafis, FSA, NFA, corel, adobe.